Imagination of Wisdom in Fairy Tales: A Symbolic Analysis of the Great Individual Archetype - Ozdemir, Uyesi Serdar Deniz; Simsek, Esma (Geleneksel Yayincilik Ltd Stl, 2025)
FairyAtales, which hold a significant place in Turkish culture, AareAa narrative genre that contains elements of the collective unconscious, blends reality with imagination, and reveals existential mysteries of memory through symbolic codes. They convey cosmic and psychomythological motifs through symbolic oppositions, embodying the principle of duality and unity in its purest form. Within this narrative universe, archetypes that represent the essence and cause of things occupy a critical position. Among these, the archetype associated with reason and wisdom isAoften personified by the Great Individual. The Great Individual acts as the most vital symbolic agent who provides rational and emotional direction to the narrative structure. As the core of the monomyth, Athis figure accompanies the hero through all stages of the initiation journey, Aprotects them from potential psychological regression, and helps them approach the sacred threshold. In chaotic narrative settings, the Great Individual restores order, functioning as a counterbalance to the shadow archetype. The shadow, as the manifestation of magnified fears, must be confronted and overcome by the hero. AThis confrontation, achie-vable only with the symbolic assistance of the Great Individual, enables the hero's cognitive and spiritual trans-formation. Thus, the contrast between the shadow and the Great Individual serves a central narrative function. The Great Individual not only personifies goodness and courage but also plays a key role in determining fate and destiny. Acting as a representative of the cosmic order, the Great Individual influences birth, marriage, and death, guiding abstract wisdom into concrete consciousness. This figure also appears as a spiritual helper in tales where a childless king receives divine aid, symbolizing the sacred continuity of lineage. Additionally, the Great Individual plays a role in resolving challenges, healing illnesses, ensuring justice, and conveying cultural values into conscious awareness through an idealized persona. In Turkish fairy tales, the Great Individual ap-pears in human forms such as H & imath;z & imath;r, the white-bearded elder, or a dervish, and occasionally in animal forms. With elevated perception, this character emerges as a guide, Ateacher, and spiritual mentor leading the hero toward self-realization. The study focuses on Turkish fairy tales compiled from Anatolia, such as Gumushane and Bayburt Fairy Tales, Taseli Fairy Tales, and Motif and Type Research in Upper Cukurova Fairy Tales. The primary goal is to deepen the understanding of the cultural codes within fairy tales, which are products of the collective memory of the nation.
MASALLARDA BİLGELİĞİN İMGELEMİ: YÜCE BİREY ARKETİPİ ÜZERİNE SEMBOLİK BİR ÇÖZÜMLEME
Keywords: Fairy tale; archetype; Great Individual; symbol; unconscious